Avaliação da resposta de três classes de solo ao uso de fontes alternativas de corretivo da acidez e de fósforo. - Costa, Marlon Gomes da (2011)
Soil acidity, high aluminum (Al3 + ) toxicity and the low availability of phosphorus (P) are the mains factors limiting crop production in the tropics. These problems are mitigated with application of correctives of acidity and phosphate fertilizers. The aim of this study was to evaluate the efficiency of the use of pó de marga (PM) as a corrective for acidity and natural phosphate from Trauíra (NPT) as a source of phosphorus for three different classes of soils, ULTISOL GRAY, VERTISOL HIDROMORPHY and PLINTHOSOLS ARGILUVIC The experiment was performed in two phases: first, we used a factorial scheme of 3 x 3 x 5 (two correctives: calcium carbonate - CC, pó de marga - PM and soil without correction - WC, three classes of soil and five incubation periods : 30, 45, 60, 75 and 90 days, with fifteen repetitions); in the next phase, were fertilized with phosphorus in pots and planted corn in a factorial 3 x 3 x 5 (the three correctives cited, the three soils and five levels of phosphorus: 15 mg dm-3 natural phosphate from „Trauíra” (NPT), 30 mg dm-3 NPT, 45 mg dm-3 NPT, 45 mg dm-3 triple superphosphate (TSP) and a control without phosphorus. The PM was efficient in raising pH and decreasing the potential acidity for the three soil classes assessed, surpassing the CC and treatment without correction, with potential use as a soil corrective. The best responses in maize cultivation occurred in Vertissolo in dry matter production, concentration, storage and efficiency of use and recovery of P, which might be related to the chemical constitution of this soil that has high levels of nutrients, especially Ca2+ and Mg2+ . Despite not having overcame the TSP, NPT had good results on these parameters, especially for the Vertissolo, even equating in some cases to the TSP. In the three classes of soil, the doses of NPT overcame the treatment without phosphorus for most parameters. The interactions of PM in combination with NPT have not showed good results. The use of NPT showed up as an alternative to soluble fertilizers, with positive effects on the development of corn, without much difference between the doses, which may be an important factor in choosing this source